Prepoznavanje i kartiranje šumskih staništa Natura 2000 u Hrvatskoj : (I) - 91E0*, aluvijalne šume s crnom johom Alnus glutinosa i običnim jasenom Fraxinus excelsior (Alno-Padion, Alnion incanae, Salicion albae) = Identification and mapping of Natura 2000 forest habitat types in Croatia (I) - 91E0*alluvial forest with black alder Alnus glutinosa and common ash Fraxinus excelsior (Alno-Padion, Alnion incanae, Salicion albae) - Plišo Vusić, Ivana (Array, 2019)
Habitat type 91E0 in Croatia extends to approximately 80,000 ha. It contains 16 types according to the National habitat classification of Croatia (NHC). They are based on phytosociological principles and are aligned with the level of association. They are: E.1. Riparian alluvial willow forests (Salicion albae Soó 1930), poplar (Populion albae Br.-Bl. 1931) and white alder forests (Alnion incanae Pawl. in Pawl. et al. 1928) Riparian alluvial willow and poplar forests (Salicion albae, Populion albae) E.1.1.1. – Salicetum albae-fragilis Soó (1930) 1958 E.1.1.2. – Salicetum albae Isller 1926 E.1.1.3. – Salici-Populetum nigrae (R. Tx. 1931) Meyer Drees 1936 E.1.2.1. – Populetum albae (Br.-Bl.) Tchou 1947 E.1.2.2. – Populetum nigro-albae Slavnić 1952 Alluvial white alder forests (Alnion incanae) E.1.3.1. – Equiseto hyemali-Alnetum incanae M. Moor 1958 E.1.3.2. – Lamio orvalae-Alnetum incanae Dakskobler 2010 E.2. Floodplain forests of pedunculate oak, black alder and narrow-leaved ash (Alnion glutinosae Malcuit 1929, Alnion incanae) Swamp and floodplain forests of black alder narrow-leaved ash (Alnion glutinosae) E.2.1.4. – Frangulo-Alnetum glutinosae Rauš (1971) 1973 E.2.1.6. – Carici elongatae-Alnetum glutinosae W. Koch 1926 ex Tx. 1931 E.2.1.7. – Leucojo-Fraxinetum angustifoliae Glavač 1959 E.2.1.9. – Carici acutiformis-Alnetum glutinosae Scamoni 1935 Alluvial and wetland forests of black alder, elms, narrow-leaved and common ash (Alnion incanae) E.2.1.1. – Fraxino angustifoliae-Ulmetum laevis Slavnić 1952 E.2.1.2. – Carici remotae-Fraxinetum excelsioris W. Koch 1926 ex Faber 1936 E.2.1.3. – Carici brizoidis-Alnetum glutinosae Horvat 1938 E.2.1.5. – Pruno-Fraxinetum angustifoliae Glavač 1960 E.2.1.8. – Stellario nemorum-Alnetum glutinosae Lohmayer 1957 The article contains a description, area of distribution in Croatia, and diagnostic indicators for each type.